2009
DOI: 10.1007/s10238-009-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginines and inflammation markers in patients with chronic kidney disease undergoing dialysis

Abstract: The aim of this study was to investigate the pro-oxidant and proinflammatory biomarkers and their relationship with dimethylarginines (DMAs) in patients at various stages of chronic kidney disease (CKD). We studied 114 CKD patients, 36 were hemodialyzed, 41 peritoneal dialyzed and 37 nondialyzed (early stage) CKD patients. The control group consisted of 31 healthy subjects. Plasma levels of asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), L-arginine, nitric oxide (NO) and proinflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
4
16
1
Order By: Relevance
“…Our arginine results were in accord with OnerIyidogan et al (21). It has been demonstrated that CKD patients lose L-arginine during dialysis (25).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our arginine results were in accord with OnerIyidogan et al (21). It has been demonstrated that CKD patients lose L-arginine during dialysis (25).…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, conflicting findings have been reported about the effect of CAPD and HD on ADMA levels (20)(21)(22)(23) (23) reported that ADMA concentrations were higher in patients undergoing HD than those having CAPD. Iyidogan et al reported that ADMA concentrations of HD and CAPD groups were higher than those of controls and HD group had significantly higher levels of ADMA than those of CAPD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…inflammation has been demonstrated (34,35). A partly discrepant finding was reported by Zoccali et al, who found normal ADMA in patients with acute inflammation and underlying chronic disease with a variable degree of renal insufficiency and a rise in ADMA once the source of inflammation was treated; no such association was found for SDMA (36).…”
Section: Discussionmentioning
confidence: 89%
“…In particular, ADMA levels were elevated more in the patients undergoing hemodialysis than in the ones undergoing peritoneal dialysis. Results from this study suggested that patients on hemodialysis are more prone to inflammation and/or oxidative stress [6]. According to Zoccali et al [7], there are four mechanisms that may explain increased level of ADMA: increased methylation of proteins, increased protein turnover, reduced DDAH activity and impaired renal excretion.…”
Section: Introductionmentioning
confidence: 70%